SOME EXTRA-UNIVERSITARY KEYS TO UNDERSTAND THE 1918 REFORM (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
This paper attempts to discover some clues that will allow us to understand or at least guide us in understanding the nature and main characters of the University reform of 1918, outside its scope clearly academics and Intra University. The author of the work felt rescue and highlight six key that your understanding to define and explain somehow the nature and features political, social and even ideological main of the student movement, namely: the productive transformation in the Argentina and especially in Cordoba; the bifacialidad of Córdoba; the Latin American spirit of the movement of 1918; the political factor; their provincial background; and the Cordoba liberal tradition.
Keywords: Córdoba; reform; tradition; liberalism; Latin America